Pelatihan Senam Hipertensi Untuk Meningkatkan Kebugaran Pada Lansia - Ceria Nurhayati; Nuh Huda; Christina Yuliastuti; Imroatul Farida; Nur Muji Astuti; Dedi Irawandi; Dul Majid; Sri Wahyu Wilujeng; Andan Peristika Didayana (Asthadarma : Jurnal Pengabdian Kepada Masyarakat, 2025)
Hypertension is a condition where blood pressure is higher than the normal limit, namely for systolic ≥140 mmHg and for diastolic ≥ 90 mmHg. Several factors associated with the occurrence of hypertension are lifestyle, family health and certain health conditions. Based on the results of observations and observations in Banjar Kemuning, it was obtained that more than 68.8% of the population suffers from hypertension. Through community service programs, education about hypertension and hypertension exercises were carried out which aimed to increase public knowledge about hypertension and hypertension exercises. The hypertension exercises that have been carried out have had a positive impact on public health in the area where previously the community did not understand how to prevent and the signs and symptoms of hypertension, as well as hypertension exercise movements.